2019
DOI: 10.1152/ajprenal.00416.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI promotes early detection of toxin-induced acute kidney injury

Abstract: Acute kidney injury (AKI) is a common cause of morbidity and mortality in hospitalized patients. Nevertheless, there is limited ability to diagnose AKI in its earliest stages through the collection of structural and functional information. Magnetic resonance imaging (MRI) is increasingly being used to provide structural and functional data that characterize the injured kidney. Dynamic contrast-enhanced (DCE) MRI is an imaging modality with robust spatial and temporal resolution; however, its ability to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Cisplatin is a potent chemotherapeutic drug, but its efficacy is often limited by its nephrotoxicity (24,26,28). It is well recognized that cisplatin may induce acute kidney injury (AKI) during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is a potent chemotherapeutic drug, but its efficacy is often limited by its nephrotoxicity (24,26,28). It is well recognized that cisplatin may induce acute kidney injury (AKI) during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound Doppler-based renal flow and velocity measurements have previously shown promise in terms of prediction of AKI in critically ill, non-COVID-19 patients [ 5 , 6 ]. Recently, dynamic contrast-enhanced MRI was identified as an early predictor of AKI in a mouse model after administration of toxins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several currently available imaging techniques can evaluate renal blood flow in AKI [57]. Dynamic contrast-enhanced MRI, which uses iron oxide nanoparticles or gadoliniumbased contrast agents with low molecular weight, can determine the spatial distribution of renal perfusion and vascular reactivity [55,[58][59][60]. Of note, single-kidney GFR/ split function can be estimated using this method [61].…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…In particular, imaging methods such as CEST imaging or SPIO nanoparticles can help to evaluate sCre-negative but damage biomarker-positive patients with subclinical or incipient AKI [ 152 ]. Privratsky et al [ 59 ] reported renal tissue damage detection using dynamic contrast-enhanced MRI after cisplatin treatment from an early stage when sCre and NGAL levels were not elevated. In the context of clinical settings, cutoff values for novel damage biomarkers and imaging information need to be evaluated against patient outcomes (e.g., need for renal replacement therapy) independent of functional biomarkers (e.g., sCre) [ 13 , 153 ].…”
Section: Utility Of Imaging Techniques In the Diagnosis And Treatment Of Akimentioning
confidence: 99%